2020
DOI: 10.35542/osf.io/jy26f
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Teaching and Learning English for Visually Impaired Students: An Ethnographic Case Study

Abstract: In this article we report an ethnographic case study of observing the teaching and learning of English at a school for visually impaired students in Bandar Lampung, Indonesia. Data collection included student and teacher interviews. It also covered class observation and used a social constructivist framework of disability. The study revealed that the students received inadequate modifications of instruction in foreign language learning. However, the students used a variety of resources with the screen reader t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…By having the further and detail explanation above, the researcher discovers that the first previous research conducted by [2] Lintangsari, Alies Poetri. Emaliana, I., (2019), the second previous research conducted [6], and the present research, have several similarities. The main engaged factors found are the teaching approach and attitudes that lecturer have while conducting the learning English process, the better engagement that students will have.…”
Section: English Examination Resultssupporting
confidence: 72%
“…By having the further and detail explanation above, the researcher discovers that the first previous research conducted by [2] Lintangsari, Alies Poetri. Emaliana, I., (2019), the second previous research conducted [6], and the present research, have several similarities. The main engaged factors found are the teaching approach and attitudes that lecturer have while conducting the learning English process, the better engagement that students will have.…”
Section: English Examination Resultssupporting
confidence: 72%
“…The learners gain not only language skill -reading, speaking, listening, and writing but also literary skillthe skills of paraphrasing, summarising and interpreting. For further research, it can be studied how literary work as authentic material can be used for teaching students with disabilities, such as visual impairment (Jenks, 2005;Susanto & Nanda, 2018), for improving students' academic literacy (Mukhroji, 2020), and for developing other teaching strategies to face students' learning problems in EFL classroom (Alquraishy, Sagban, & AlMumar, 2020;Huwari, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This journal indicated that the hearing impaired students are no more able likely than hearing students to be visual learners and are no stronger in their visual skills and habits with sign language skills. The third journal by Susanto and Nanda (2018) entitled "Teaching and Learning English for Visually Impaired Students: An Ethnographic Case Study". This research discussed on the teaching and learning of English at school of impaired students.…”
Section: Hearing Impaired Students In Learning English Vocabulariesmentioning
confidence: 99%